Melatonin Alleviates Copper Toxicity via Improving ROS Metabolism and Antioxidant Defense Response in Tomato Seedlings - Tao Zhang; Yong Wang; Xiaojing Ma; Zhaopeng Ouyang; Lei Deng; Shunshan Shen; Xiaoxing Dong; Nanshan Du; Han Dong; Zhixin Guo; Geng Meng; Fengzhi Piao; et al. (MDPI AG, 2022)
The excessive accumulation of copper (Cu2+) has become a threat to worldwide crop production. Recently, it was revealed that melatonin (MT) could play a crucial role against heavy metal (HM) stresses in plants. However, the underlying mechanism of MT function acted upon by Cu2+ stress (CS) has not been substantiated in tomatoes. In the present work, we produced MT-rich tomato plants by foliar usage of MT, and MT-deficient tomato plants by employing a virus-induced gene silencing methodology and exogenous foliar application of MT synthesis inhibitor para-chlorophenylalanine (pCPA). The obtained results indicate that exogenous MT meaningfully alleviated the dwarf phenotype and impeded the reduction in plant growth caused by excess Cu2+. Furthermore, MT effectively restricted the generation of reactive oxygen species (ROS) and habilitated cellular integrity by triggering antioxidant enzyme activities, especially via CAT and APX, but not SOD and POD. In addition, MT increased nonenzymatic antioxidant activity, including FRAP and the GSH/GSSG and ASA/DHA ratios. MT usage improved the expression of several defense genes (CAT, APX, GR and MDHAR) and MT biosynthesis-related genes (TDC, SNAT and COMT). Taken together, our results preliminarily reveal that MT alleviates Cu2+ toxicity via ROS scavenging, enhancing antioxidant capacity when subjected to excessive Cu2+. These results build a solid foundation for developing new insights to solve problems related to CS.